Policy implementation is operational - Omamo, Steven Were (International Food Policy Research Institute, 2025)
This paper argues that policy implementation must be understood as a fundamentally operational process, not merely the execution of policy intent. It proposes a framework centered on four core dimensions of implementation: activation cost, option value, kinetics, and negotiation. Drawing on the case of the World Food Programme’s 2008 Cash and Voucher Policy, the paper shows that implementing a policy requires building physical and institutional systems, creating delivery capacity, managing uncertainty, and preserving strategic flexibility. The case is not about cash transfers as such, but about what it took—organizationally, technically, and politically—for the World Food Programme to move from a policy decision to sustained, system wide operational capability and delivery. The paper concludes that successful policy implementation depends on treating implementation itself as the central frontier of policy action—requiring investment, learning, negotiation, and time. Several implications emerge for researchers, practitioners, and investors seeking to close the gap between policy on paper and policy in action.